LEGAL LIABILITY OF BANKS FOR CUSTOMER LOSSES RESULTING FROM SKIMMING FROM THE PERSPECTIVE OF ELECTRONIC TRANSACTION SECURITY - Aditya Tri Hardiyawan; Sanusi; Soesi Idayanti (RADJA PUBLIKA, 2026)
Banks are among the financial institutions that play a highly significant role in a country's economy. Their function as both custodians of funds and financial intermediaries is widely recognized as beneficial to society and the business sector. Today, convenience and transaction speed have become key priorities for banks in delivering services to their customers. Various banking services have adopted information technology that has become an integral part of everyday use, including online banking services, Automated Teller Machine (ATM) networks, Electronic Data Capture (EDC) networks, phone banking services, internet banking services, credit card services, installment card services, and other deferred payment facilities. This study aims to examine the legal liability of banks for customer losses resulting from skimming from the perspective of electronic transaction security. The research employs a library research method. The approach adopted in this study is a normative legal approach. The primary legal materials consist of statutory regulations with binding legal force, including: Law Number 10 of 1998 concerning Banking; Law Number 11 of 2008 concerning Electronic Information and Transactions, as amended by Law Number 19 of 2016; Law Number 8 of 1999 concerning Consumer Protection; and Financial Services Authority Regulation Number 1/POJK.07/2013 concerning Consumer Protection in the Financial Services Sector. In fulfilling their legal responsibility and providing services to customers to prevent skimming, banks have adopted security technologies such as two-factor authentication (2FA), data encryption, and biometric authentication (such as fingerprint and facial recognition) to enhance the protection of customer data and transactions. In addition, banks comply with policy directives issued by the Indonesian banking authorities by adhering to the applicable regulatory framework to ensure legal certainty and customer satisfaction. Keywords: Legal Liability, Banking, Skimming, Electronic Transactions).